Litterfall and Nutrients Return in Poplar Plantation Varying in Row Directions and Spacings - Singh, Baljit; Gill, Rishi; Kaur, Navneet (Indian Journal of Agroforestry, 2020)
Litterfall addition from tree species leads to organic matter replenishment and a considerable amount of nutrients return to the soil. The study on litterfall addition and nutrients return was conducted in five years old poplar plantation established in a replicated randomized block design having combinations of two row directions (North-South and East-West) and three spacings (5 x 4 m, 8 x 2.5 m and 11 x 3 m, diagonally paired at 2 m). The total litterfall addition was significantly higher in 5 x 4 m (5621 kg ha-1) and 8 x 2.5 m (5479 kg ha-1) spacings than 11 x 3 m, paired (4912 kg ha-1), whereas direction did not have significant effect on litterfall addition. Litterfall was significantly higher during November (1721 kg ha-1) and December (1768 kg ha-1)than the other months. Concentration of different macro and micronutrients differed significantly during different months, but it did not follow a definite pattern. Concentration of Ca (1.73-1.98%) and Fe (1325-1463 ppm) was maximum among the different macro and micronutrients, respectively during different months. The return of different nutrients was significantly higher during November and December than other months. The total return of nutrients through litterfall was significantly higher in 5 x 4 m and 8 x 2.5 m spacings than 11 x 3 m (paired). Total return of Ca in different spacing was maximum (86.7-103.5 kg ha-1) followed by N (44.4-53.1 kg ha-1) amongst different macronutrients, whereas the return of P was minimum (5.97-7.30 kg ha-1).Among the different micronutrients, the total return of Fe was maximum (6854-7767 g ha-1) and that of Cu, minimum Â (103.1-115.6 g ha-1) in the different spacings.